2017
DOI: 10.7150/ijbs.20132
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle-Specific Overexpression of PGC-1α Induces Fiber-Type Conversion through Enhanced Mitochondrial Respiration and Fatty Acid Oxidation in Mice and Pigs

Abstract: Individual skeletal muscles in the animal body are heterogeneous, as each is comprised of different fiber types. Type I muscle fibers are rich with mitochondria, and have high oxidative metabolisms while type IIB fibers have few mitochondria and high glycolytic metabolic capacity. Peroxisome proliferator-activated receptor gamma coactivator 1α (PGC-1α), a transcriptional co-activator that regulates mitochondrial biogenesis and respiratory function, is implicated in muscle fiber-type switching. Over-expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 38 publications
0
63
0
Order By: Relevance
“…PGC‐1α is known to induce a fast‐ to slow‐fiber type transition through its activation of target genes involved in substrate metabolism . Skeletal muscle‐specific overexpression of PGC‐1α induces fiber‐type conversion through enhanced mitochondrial respiration and fatty acid oxidation in mice and pigs . Therefore, our results suggest that oral 6‐gingerol not only improves mitochondrial dysfunctional structure but also increases high endurance type I fiber (MyHC1) content by activating AMPK/PGC‐1α signaling to enhance mitochondrial function and muscle oxidative capacity in ageing rats.…”
Section: Discussionmentioning
confidence: 54%
“…PGC‐1α is known to induce a fast‐ to slow‐fiber type transition through its activation of target genes involved in substrate metabolism . Skeletal muscle‐specific overexpression of PGC‐1α induces fiber‐type conversion through enhanced mitochondrial respiration and fatty acid oxidation in mice and pigs . Therefore, our results suggest that oral 6‐gingerol not only improves mitochondrial dysfunctional structure but also increases high endurance type I fiber (MyHC1) content by activating AMPK/PGC‐1α signaling to enhance mitochondrial function and muscle oxidative capacity in ageing rats.…”
Section: Discussionmentioning
confidence: 54%
“…PPARβ was shown to be required for the formation and maintenance of slow oxidative fibres in skeletal muscles by stimulating PGC‐1α expression (Schuler et al., ). The overexpression of PGC‐1α was previously reported to increase the proportion of type I fibres in the gastrocnemius muscle (Lin et al., ; Zhang et al., ). In the present study, increases in the proportion of type I fibres were observed in SOL only (Table ).…”
Section: Discussionmentioning
confidence: 89%
“…PGC‐1α also contributes to the changes induced in muscle fibre type by exercise training. Although the muscle‐specific deletion of PGC‐1α did not affect exercise‐induced fibre type transformation (Geng et al., ), the overexpression of PGC‐1α was shown to increase the proportion of type I fibres in skeletal muscle (Lin et al., ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, our data indicated that inhibition of AMPK and Sirt1 significantly attenuated the leucine‐induced increase in the expression of mitochondrial biogenesis and function‐related genes, suggesting that leucine modulated mitochondrial biogenesis via Sirt1/AMPK signaling, which is consistent with a previous study in C2C12 cells (Lin et al., ). Additionally, a recent in vitro study also found that skeletal muscle‐specific overexpression of PGC‐1α promotes the formation of slow‐twitch muscle fibers through enhanced mitochondrial function in mice and pigs (Zhang et al., ). However, whether leucine increases the expression of slow oxidative fiber by changing the mitochondrial function needs to be further investigated.…”
Section: Discussionmentioning
confidence: 98%